Discourses of tourism in the official tourism websites in Southeast Asia - Muhammad Salim, Muhammad Arfin (2015)
Today, as one of the biggest population movements and one of the world’s largest economic activities, tourism has become one of the more desirable areas to be investigated. Tourism promotional documents contain detailed description of potential destinations. However, very few research, if any, have focused on investigating the text and visual images in portraying the destination image on official tourism websites. This research employed a qualitative research design underpinned by the Social Constructionism theory. In addition, discourse analysis and multimodality were utilized to describe the discourses of tourism by investigating the integration of language use and visual images in portraying the tourist destinations on the official tourism websites of Southeast Asian countries. This study aims to provide an in-depth and comprehensive understanding of the tourism discourse, in particular, the official tourism websites of four top tourism destinations in Southeast Asia that is Malaysia, Thailand, Singapore and Indonesia. Data were collected via online documentation and semi structured interview and analysed using both textual and visual analysis. The former included lexical and syntactical strategies, while the visual analysis focused on the analysis of salience and modality elements. The findings of the study revealed that various discourses of tourism like the discourse of diversity, and discourse of spirituality realized through textual and visual means are used to portray the destination image. Finally, the study has significant contribution to discourse driven research and has application for tourism website development